Strategi Pustakawan Universitas Andalas dalam Transfer Knowledge Pemustaka melalui Model SECI - Olivia, Dea; Marlini, Marlini; Desriyeni, Desriyeni (TSAQOFAH, 2026)
The library paradigm in the digital era has undergone a significant transformation from merely serving as a repository of collections to becoming a center for the management and dissemination of knowledge, thereby positioning librarians as knowledge facilitators who assist the academic community in accessing, understanding, and utilizing information effectively. This study aims to analyze the strategies of librarians at Universitas Andalas in transferring knowledge to library users through the implementation of the SECI (Socialization, Externalization, Combination, Internalization) model. The study employs a descriptive qualitative approach with data collected through observation and document analysis, and analyzed using the Miles and Huberman model. The findings show that all four stages of the SECI model have been implemented systematically: socialization through direct interaction and personal assistance, externalization through the preparation of guidelines and digital tutorials, combination through the integration of various sources of explicit information, and internalization through the enhancement of students’ abilities in digital literacy and scientific citation ethics. These results underscore that successful knowledge transfer in libraries depends not only on technological infrastructure but also on interpersonal communication, a culture of knowledge sharing, and the competencies of librarians as learning agents. This study contributes to strengthening the perspective of knowledge management in university library settings and can serve as a reference for the development of SECI-based service strategies in the future.